Corrosion Resistant Coating from Nano Printed Circuit Board Powder for the Reinforced Concrete Structures - R. Mohana; D. Selvaganesh; A. Anto Issac; M. Vignesh Kumar (Advances in Materials Science and Engineering)
Corrosion in steel leads to the deterioration of reinforced concrete structures due to chemical reactions between steel and its surrounding atmosphere. In this paper, a novel anticorrosive powder was derived from the waste Printed Circuit Board (PCB) and manually coated on the steel rebar of the reinforced concrete specimen. The corrosion-resistant efficiency of the developed nano PCB-coating on the steel bars was studied by polarization, electrochemical impedance spectroscopy, and accelerated corrosion technique. Also, the applicability of the nano PCB-coated rebar as reinforcement in the concrete environment was investigated. From the results, it was observed that the nano PCB-coated specimens exhibited 3.5 times reduced rate of corrosion and lost only 46.15% strength and 52.5% diameter under the accelerated rate of 6 V after 48 hours. The presence of nano PCB powder improved the corrosion-resistant behaviour of the steel rebar by 1.65 times of the noncoated specimen. Also, the nano PCB-coating reduced the loss in residual yield strength of the corroded steel rebar by 32% lesser than the noncoated specimens and exhibited similar corrosion-resistant properties as that of the existing zinc coating. In addition to the corrosion resistance, the nano PCB-coated steel rebar exhibited almost similar adhesion with concrete as that of the commercial zinc coating which is 7% lower than uncoated steel rebars. It was inferred from this research work that the proposed anticorrosive coating prepared from the waste nano PCB powder showed better corrosion-resistant behaviour and reduced the overall cost of coating by 42%, which ensures economy and serviceability.